Pharmacokinetics and pharmacodynamics of sibrafiban alone or in combination with ticlopidine and aspirin - Wittke, Bärbel (Blackwell Science Inc, 2000)
AIMS: The purpose of this clinical study was to evaluate the effects of a ticlopidine/aspirin combination on the pharmacokinetics and pharmacodynamics of sibrafiban and the tolerability of the combination therapy METHODS: Thirty-eight healthy male volunteers were randomized to receive one of the following treatments for 7 days: sibrafiban (n = 12), ticlopidine/aspirin (n = 12), or the combination treatment sibrafiban/ticlopidine/aspirin (n = 14). Concentrations of the active metabolite of sibrafiban, Ro 44–3888, in plasma and urine were determined by column-switching liquid chromatography combined with tandem mass spectrometry. The pharmacodynamics of sibrafiban and ticlopidine/aspirin were examined by measuring the inhibition of ADP- or collagen-induced platelet aggregation. RESULTS: The addition of ticlopidine/aspirin to sibrafiban did not significantly alter the pharmacokinetic parameters of Ro 44–3888. the geometric mean ratio for AUC(0,12h) was 110 (95% CI 0.82, 1.22). Separately, sibrafiban and ticlopidine/aspirin inhibited ADP-and collagen-induced platelet aggregation and the effects of the two treatments were additive. For example, the average inhibition of ADP-induced platelet aggregation over 12 h was 42% in the sibrafiban treated group, 55% in the ticlopidine/aspirin group and 69% in the sibrafiban/ticlopidine group. The bleeding time was prolonged in the treatments with ticlopidine/aspirin (8.1 min) and sibrafiban/ticlopidine/aspirin (8.6 min) compared with sibrafiban alone (3.5 min). CONCLUSIONS: This study shows a significant pharmacodynamic interaction between sibrafiban and ticlopidine/aspirin. Consequently, the simultaneous administration of sibrafiban and ticlopidine/aspirin should be carefully monitored to ensure the patient's coverage with an antiplatelet drug without exposure to an excessive bleeding risk.